Mechanical Analysis of Bone-Plate Construct Regarding Strength and Stiffness - Abed, Rana Idan; Abbas, Sadiq Jaafer; Alsaadan, Walead Abd Al-Hasan (Al-Nahrain Journal for Engineering Sciences, 2020)
The aim of this study was to support surgeons to decide where to place the screws in order to achieve an optimal fracture healing and to prevent implant failure after a femoral shaft fracture So this paper focus on the analysis of bone-plate construct by using Finite element Analysis (FEA), comminuted femur fractured bone fixed with Dynamic Compression Plate (DCP) 16 holes by 4.5 Cortex screws, to investigate the effects of screws configuration on the mechanical behavior of different seven model as Interfragmentary strain which is the most important factor for femur fracture healing. The results state the relationships between the Von-Mises stress, Total deformation and Interfragmentary strain with respect to the screws configuration. The study shows the regions of maximum stress from stress distribution and also founded that we can decrease the Interfragmentary strain by increasing the number of screws.